MEMAKAN HARTA SECARA BATIL (Perspektif Surat An-Nisa: 29 dan At-Taubah: 34) - taufiq, taufiq (JURIS (Jurnal Ilmiah Syariah), 2018)
The Quran mentions the term treasure in some letters with various derevasion. The mention of the word treasure is accompanied by the procedure of acquisition or utilization. One of them is the prohibition of consuming treasure in a vanity way. As many as 36 times a word that means vanity is mentioned in the Quran, including An- Nisa: 29 and At- Taubah: 34. Using a thematic interpretation approach, explores some of the ethical messages contained in these two verses. Forbidden treasures managed by vile. Indications of vanity include the emergence of disillusionment with the parties and be classified as zalim.